Advanced Imaging Technology in Biliary Tract Diseases:Narrow-Band Imaging of the Bile Duct - Hyun Jong Choi; Jong Ho Moon; Yun Nah Lee (Korean Society of Gastrointestinal Endoscopy, 2015)
Newly introduced direct peroral cholangioscopy and the development of video choledochoscopes have enabled more defined observation of bile duct mucosal lesions with clearer images. Narrow-band imaging (NBI) is a unique endoscopic imaging technology that provides enhanced endoscopic images of surface mucosal structures and its superficial microvessels. Advanced cholangioscopy and NBI are expected to be useful for precise evaluation and correct diagnosis of biliary tract diseases. However, the diagnostic value of advanced bile duct imaging with cholangioscopy requires further evaluation.